A structural investigation of quantitative easing - Gregor Böhl; Gavin Goy; Felix Strobel (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2020)
Did the Federal Reserves' Quantitative Easing (QE) in the aftermath of the financial crisis have macroeconomic effects? To answer this question, the authors estimate a large-scale DSGE model over the sample from 1998 to 2020, including data of the Fed's balance sheet. The authors allow for QE to affect the economy via multiple channels that arise from several financial frictions. Their nonlinear Bayesian likelihood approach fully accounts for the zero lower bound on nominal interest rates. They find that between 2009 to 2015, QE increased output by about 1.2 percent. This reflects a net increase in investment of nearly 9 percent, that was accompanied by a 0.7 percent drop in aggregate consumption. Both, government bond and capital asset purchases were effective in improving financing conditions. Especially capital asset purchases significantly facilitated new investment and increased the production capacity. Against the backdrop of a fall in consumption, supply side effects dominated which led to a mild disinflationary effect of about 0.25 percent annually.
urn:nbn:de:hebis:30:3-542738
Keywords: E63; C63; E58; E32; C62; 330; Quantitative Easing; Liquidity Facilities; Zero Lower Bound; Nonlinear Bayesian Estimation